Preparation method of polypyrrole-coated Prussian blue positive electrode composite material

The Prussian blue wet material was prepared by co-precipitation method and polypyrrole coated in aqueous alcohol solution, which solved the problem of Prussian blue structural instability, achieved a more uniform coating layer, and significantly improved the cycle stability of the positive electrode material.

CN116409801BActive Publication Date: 2025-03-14GANZHOU LITAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211719749.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-14
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The traditional Prussian blue cathode material has an unstable structure during drying, which affects its cycle stability, and there is a problem of uneven coating in the solid phase coating method.

Method used

The Prussian blue wet material was prepared by co-precipitation method and polypyrrole coated in an aqueous alcohol solution. Polypyrrole was initiated by initiating polymerization to form a uniform polypyrrole coated layer.

Benefits of technology

The uniformity of the polypyrrole cladding layer is improved, the influence of water on Prussian blue is reduced, and the circulation stability of the cathode material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116409801B_ABST
    Figure CN116409801B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a method for preparing a polypyrrole-coated Prussian blue positive electrode composite material. The present invention first mixes sodium ferrocyanide, a first soluble sodium salt and water to obtain a first mixed solution; secondly mixes a soluble divalent transition metal salt, a second soluble sodium salt and water to obtain a second mixed solution; thirdly mixes the first mixed solution, the second mixed solution and a complexing agent to perform a coprecipitation reaction to obtain a Prussian blue wet material; fourthly mixes the Prussian blue wet material, pyrrole, water and an alcohol solvent to obtain a liquid to be treated; fifthly mixes the liquid to be treated and an initiator to obtain the polypyrrole-coated Prussian blue positive electrode composite material; the first soluble sodium salt and the second soluble sodium salt do not include sodium ferrocyanide. The method provided by the present invention can improve the coating uniformity of the polypyrrole layer and improve the cycle stability of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and particularly relates to a preparation method of a polypyrrole-coated Prussian blue cathode composite material. Background Art

[0002] With the continuous development of global lithium resources, the cost of lithium resources has been remaining high, and lithium ion batteries are gradually losing competitiveness in the field of large-scale energy storage. Sodium ion batteries, compared with lithium ion batteries, have more advantages in cost and better application prospects in the field of large-scale energy storage.

[0003] Prussian blue compounds are a common cathode material for sodium ion batteries, with the chemical formula of Na x M[Fe(CN)6] y ·zH2O (where the value range of x is 0 < x < 2, the value range of y is 0 < y < 1, and M is a transition metal), which have the characteristics of high specific capacity, long cycle life and excellent low-temperature performance, and the raw material cost is low and the synthesis method is simple.

[0004] The preparation method of Prussian blue generally adopts the co-precipitation method, and the obtained Prussian blue often contains more crystal water and vacancy defects. During the subsequent drying process, the water in Prussian blue is dried, resulting in the instability of its structure and affecting its cycle stability. Usually, measures such as coating Prussian blue are adopted for improvement;

[0005] The traditional coating method is mainly the solid-phase coating method, but the solid-phase coating method has the problem of uneven coating, which further affects the cycle stability of the finally obtained cathode material. Summary of the Invention

[0006] The purpose of the present invention is to provide a preparation method of a polypyrrole-coated Prussian blue cathode composite material, and the method provided by the present invention can further improve the uniformity of the polypyrrole coating layer and improve the cycle stability of the cathode material.

[0007] In order to achieve the above purpose, the present invention provides the following technical solutions:

[0008] The present invention provides a preparation method of a polypyrrole-coated Prussian blue cathode composite material, including the following steps:

[0009] Mix sodium ferrocyanide, a first soluble sodium salt and water for the first time to obtain a first mixed solution;

[0010] Mix a soluble divalent transition metal salt, a second soluble sodium salt and water for the second time to obtain a second mixed solution;

[0011] Mix the first mixed solution, the second mixed solution and a complexing agent for the third time, and carry out a co-precipitation reaction to obtain a wet Prussian blue material;

[0012] fourthly mixing the wet Prussian blue material, pyrrole, water and alcohol solvent to obtain a liquid to be treated;

[0013] fifthly mixing the liquid to be treated and the initiator to obtain the polypyrrole-coated Prussian blue positive electrode composite material;

[0014] The first soluble sodium salt and the second soluble sodium salt do not include sodium ferrocyanide.

[0015] Preferably, the first soluble sodium salt and the second soluble sodium salt independently include one or more of sodium chloride, sodium citrate, sodium alginate, disodium edetate, sodium oxalate, sodium acetate, sodium gluconate and sodium pyrophosphate.

[0016] Preferably, the soluble divalent transition metal salt includes a soluble divalent manganese salt and a soluble divalent iron salt.

[0017] Preferably, the molar ratio of the sodium ferrocyanide to the first soluble sodium salt is 1:1 to 1.8;

[0018] The concentration of sodium ferrocyanide in the first mixed solution is 0.16-0.64 mol / L.

[0019] Preferably, the molar ratio of the soluble divalent transition metal salt to the second soluble sodium salt is 1:2-5;

[0020] The concentration of the soluble divalent transition metal salt in the second mixed solution is 0.32-0.96 mol / L.

[0021] Preferably, the complexing agent includes a nitrogen-containing complexing agent;

[0022] The molar ratio of sodium ferrocyanide to the complexing agent in the first mixed solution is 0.32:1-2.5;

[0023] The molar ratio of the sodium ferrocyanide in the first mixed solution to the soluble divalent transition metal salt in the second mixed solution is 0.32:0.4-1.

[0024] Preferably, the coprecipitation reaction temperature is 0-30°C.

[0025] Preferably, the moisture content of the Prussian blue wet material is 60% to 70%;

[0026] The usage ratio of the Prussian blue wet material to pyrrole is 50g:1-10mL.

[0027] Preferably, the alcohol solvent includes one or more of ethanol, methanol and ethylene glycol;

[0028] The volume ratio of water to alcohol solvent is 1 to 3:1;

[0029] The concentration of Prussian blue in the liquid to be treated is 0.50.7 g / mL.

[0030] Preferably, the initiator includes one or more of ammonium persulfate, hydrogen peroxide, potassium persulfate and sodium persulfate;

[0031] The mass ratio of the initiator to the Prussian blue wet material is 1-2:10.

[0032] The present invention provides a method for preparing a polypyrrole-coated Prussian blue positive electrode composite material, comprising the following steps: first mixing sodium ferrocyanide, a first soluble sodium salt and water to obtain a first mixed solution; second mixing a soluble divalent transition metal salt, a second soluble sodium salt and water to obtain a second mixed solution; third mixing the first mixed solution, the second mixed solution and a complexing agent to perform a coprecipitation reaction to obtain a Prussian blue wet material; fourth mixing the Prussian blue wet material, pyrrole, water and an alcohol solvent to obtain a to-be-treated liquid; fifth mixing the to-be-treated liquid and an initiator to obtain the polypyrrole-coated Prussian blue positive electrode composite material; the first soluble sodium salt and the second soluble sodium salt do not include sodium ferrocyanide. The present invention obtains a Prussian blue wet material by a coprecipitation method, and is coated in an alcohol aqueous solution without drying treatment, so as to reduce the activity of water, reduce the influence of water on Prussian blue, and thus improve the cycle stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the polypyrrole-coated Prussian blue positive electrode composite material obtained in Example 1;

[0034] Figure 2 This is the XRD pattern of the polypyrrole-coated Prussian blue positive electrode composite material obtained in Example 1;

[0035] Figure 3 The first charge and discharge curve of a sodium ion half-cell assembled with the polypyrrole-coated Prussian blue positive electrode composite material obtained in Example 1 as the positive electrode material;

[0036] Figure 4 This is a cycle performance diagram of a sodium ion half-cell assembled using the polypyrrole-coated Prussian blue positive electrode composite material obtained in Example 1 as the positive electrode material;

[0037] Figure 5 This is a rate performance diagram of a sodium ion half-cell assembled using the polypyrrole-coated Prussian blue positive electrode composite material obtained in Example 1 as the positive electrode material. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a polypyrrole-coated Prussian blue positive electrode composite material, comprising the following steps:

[0039] mixing sodium ferrocyanide, a first soluble sodium salt and water to obtain a first mixed solution;

[0040] Mixing the soluble divalent iron salt, the second soluble sodium salt and water for a second time to obtain a second mixed solution;

[0041] The first mixed solution, the second mixed solution and the complexing agent are mixed for a third time, and a coprecipitation reaction is performed to obtain a Prussian blue wet material;

[0042] fourthly mixing the wet Prussian blue material, pyrrole, water and alcohol solvent to obtain a liquid to be treated;

[0043] fifthly mixing the liquid to be treated and the initiator to obtain the polypyrrole-coated Prussian blue positive electrode composite material;

[0044] The first soluble sodium salt and the second soluble sodium salt do not include sodium ferrocyanide.

[0045] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0046] The present invention first mixes sodium ferrocyanide, a first soluble sodium salt and water to obtain a first mixed solution.

[0047] In the present invention, the first soluble sodium salt preferably includes one or more of sodium chloride, sodium citrate, sodium alginate, disodium ethylenediaminetetraacetate, sodium oxalate, sodium acetate, sodium gluconate and sodium pyrophosphate; when the first soluble sodium salt includes two or more of the above options, the present invention has no special limitation on the ratio of specific substances, and they can be mixed in any ratio.

[0048] In the present invention, the molar ratio of the sodium ferrocyanide to the first soluble sodium salt is preferably 1:1-1.8, more preferably 1:1.2-1.7, and more preferably 1:1.3-1.5. In the present invention, the concentration of sodium ferrocyanide in the first mixed solution is preferably 0.16-0.64 mol / L, more preferably 0.20-0.60 mol / L, and more preferably 0.25-0.55 mol / L.

[0049] The present invention has no particular limitation on the first mixing process, and the first mixing process may be performed using a process well known to those skilled in the art.

[0050] The present invention secondly mixes a soluble divalent transition metal salt, a second soluble sodium salt and water to obtain a second mixed solution.

[0051] In the present invention, the soluble divalent transition metal salt preferably includes a soluble divalent manganese salt and a soluble divalent iron salt. In the present invention, the soluble divalent iron salt preferably includes one or more of ferrous chloride, ferrous sulfate and ferrous nitrate; when the soluble divalent transition metal salt is preferably two or more of the above selections, the present invention has no special restrictions on the ratio of the specific substances, and they can be mixed in any ratio.

[0052] In the present invention, the type of the second soluble sodium salt is the same as the type of the first soluble sodium salt, which will not be described in detail herein.

[0053] In the present invention, the molar ratio of the soluble divalent transition metal salt to the second soluble sodium salt is preferably 1:2 to 5, more preferably 1:3 to 4. In the present invention, the concentration of the soluble divalent transition metal salt in the second mixed solution is preferably 0.32 to 0.96 mol / L, more preferably 0.40 to 0.90 mol / L, and more preferably 0.50 to 0.80 mol / L.

[0054] The present invention has no particular limitation on the second mixing process, and the second mixing process may be performed using a process well known to those skilled in the art.

[0055] The present invention mixes the first mixed solution, the second mixed solution and the complexing agent for a third time, and performs a coprecipitation reaction to obtain a Prussian blue wet material.

[0056] In the present invention, the complexing agent preferably includes a nitrogen-containing complexing agent. In the present invention, the nitrogen-containing complexing agent preferably includes one or more of concentrated ammonia, ammonium chloride, ammonium fluoride, ammonium bromide, ammonium iodide, ammonium acetate, ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium chloride, ammonium sulfate and ammonium nitrate.

[0057] In the present invention, the molar ratio of sodium ferrocyanide in the first mixed solution to the soluble divalent transition metal salt in the second mixed solution is preferably 0.32:0.4-1, more preferably 0.32:0.5-0.9, and more preferably 0.32:0.6-0.8. In the present invention, the molar ratio of sodium ferrocyanide to the complexing agent in the first mixed solution is preferably 0.32:1-2.5, more preferably 0.32:1.2-2.3, and more preferably 0.32:1.5-2.0.

[0058] In the present invention, the complexing agent is preferably added in the form of a complexing agent solution. In the present invention, the mass concentration of the complexing agent in the complexing agent solution is preferably 25g / L to 50g / L. In the present invention, the pH value of the complexing agent solution is preferably 6 to 8. The present invention has no special restrictions on the preparation method of the complexing agent solution, and the complexing agent and water can be directly mixed. In the present invention, when the complexing agent is concentrated ammonia water, after the concentrated ammonia water and water are mixed, it is also preferably included to add a pH value regulator to adjust the pH value. In the present invention, the mass concentration of the concentrated ammonia water is preferably 28%. In the present invention, the pH value regulator preferably includes one or more of ammonium chloride, ammonium fluoride, ammonium bromide, ammonium iodide, ammonium acetate, ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium chloride, ammonium sulfate and ammonium nitrate. The present invention has no special restrictions on the process of pH adjustment, and the process well known to those skilled in the art can be adopted.

[0059] In the present invention, the third mixing preferably includes:

[0060] Under stirring conditions, the second mixed solution and the complexing agent solution are dropped into the first mixed solution.

[0061] The present invention has no particular limitation on the stirring condition parameters, and those skilled in the art may be used.

[0062] In the present invention, the drop rate of the second mixed solution is preferably 1 to 5 mL / min, more preferably 2 to 4 mL / min. In the present invention, the drop rate of the complexing agent solution is preferably 1 to 2 mL / min.

[0063] In the present invention, the temperature of the coprecipitation reaction is preferably 0 to 30°C, more preferably 2 to 25°C, and even more preferably 5 to 20°C.

[0064] In the present invention, the coprecipitation reaction begins when the second mixed solution and the complexing agent solution are dripped into the first mixed solution. In the present invention, the coprecipitation reaction time includes the dripping time of the second mixed solution and the complexing agent solution and the continuous stirring time after the dripping is completed. In the present invention, the dripping time is preferably 1 to 5 hours; the continuous stirring time is preferably 2 to 5 hours.

[0065] After the coprecipitation reaction, the present invention also preferably includes sequentially aging and centrifuging the obtained product.

[0066] In the present invention, the aging time is preferably 4 to 15 hours, and the temperature is preferably 20 to 30° C. The present invention has no particular limitation on the centrifugal washing process, and the process well known to those skilled in the art can be used.

[0067] In the present invention, the moisture content of the Prussian blue wet material is preferably 60% to 70%.

[0068] After obtaining the Prussian blue wet material, the present invention fourthly mixes the Prussian blue wet material, pyrrole, water and an alcohol solvent to obtain a liquid to be treated.

[0069] In the present invention, the dosage ratio of the Prussian blue wet material to pyrrole is preferably 50g:1-5mL, more preferably 50g:2-4mL, and more preferably 50g:2-3mL. In the present invention, the alcohol solvent preferably includes one or more of ethanol, methanol and ethylene glycol; the volume ratio of water to alcohol solvent is preferably 1-3:1; the concentration of Prussian blue in the liquid to be treated is preferably 0.5-0.7g / mL, more preferably 0.6g / mL.

[0070] In the present invention, the fourth mixing is preferably carried out under stirring. The present invention has no special limitation on the stirring condition parameters, and those known to those skilled in the art can be used. In the present invention, the temperature of the fourth mixing is preferably 0 to 5° C. In a specific embodiment of the present invention, the fourth mixing is preferably carried out in a cold water bath.

[0071] After obtaining the liquid to be treated, the present invention fifthly mixes the liquid to be treated and an initiator to obtain the polypyrrole-coated Prussian blue positive electrode composite material.

[0072] In the present invention, the initiator preferably includes one or more of ammonium persulfate, hydrogen peroxide, potassium persulfate and sodium persulfate. In the present invention, the mass ratio of the initiator to the Prussian blue wet material is preferably 1 to 2:10.

[0073] In the present invention, the initiator is preferably added in the form of an initiator solution. In the present invention, the mass concentration of the initiator solution is preferably 0.1 to 0.5 g / mL.

[0074] In the present invention, the fifth mixing preferably includes:

[0075] The initiator solution is added to the liquid to be treated under stirring. In the present invention, the initiator solution is preferably pre-cooled before being added; the temperature of the initiator solution after the pre-cooling treatment is preferably 0-8°C.

[0076] The present invention has no special limitation on the stirring condition parameters, and the stirring condition parameters known to those skilled in the art can be adopted. In the present invention, the addition rate of the initiator solution is preferably 0.5 to 2 mL / min. In the present invention, the initiator solution is preferably added by a peristaltic pump.

[0077] In the present invention, the temperature of the fifth mixing is preferably 0-10°C.

[0078] After the fifth mixing, the present invention further preferably includes filtering, washing and drying the obtained material in sequence. The present invention has no particular limitation on the filtering, washing and drying process, and the filtering, washing and drying process can be performed using a process well known to those skilled in the art.

[0079] The preparation method provided by the invention has simple process, low cost, short cycle and low energy consumption, and is suitable for industrial production.

[0080] In order to further illustrate the present invention, the preparation method of a polypyrrole-coated Prussian blue positive electrode composite material provided by the present invention is described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0081] Example 1

[0082] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium chloride and 100 mL of water to obtain a first mixed solution;

[0083] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium chloride and 100 mL of water to obtain a second mixed solution;

[0084] 75 mL of 28% concentrated ammonia water and 100 mL of deionized water were mixed, and the pH value was controlled within the range of 7 to 7.5 using 1 mol / L ammonium chloride solution to obtain a complexing agent solution;

[0085] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min and the complexing agent solution was added dropwise to the first mixed solution at a dropping speed of 1 mL / min. After the addition was completed, the mixture was stirred for 2 hours to perform a coprecipitation reaction. After the obtained liquid was aged for 12 hours, it was centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%).

[0086] Under ice-water bath and stirring conditions, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 3:2), and then 1 mL of pyrrole was added to obtain a solution to be treated;

[0087] 9.13 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0088] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0089] Example 2

[0090] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium chloride and 100 mL of water to obtain a first mixed solution;

[0091] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium chloride and 100 mL of water to obtain a second mixed solution;

[0092] 75 mL of 28% concentrated ammonia water and 100 mL of deionized water were mixed, and the pH value was controlled within the range of 7 to 7.5 using 1 mol / L ammonium chloride solution to obtain a complexing agent solution;

[0093] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min and the complexing agent solution was added dropwise to the first mixed solution at a dropping speed of 1 mL / min. After the addition was completed, the mixture was stirred for 2 hours to perform a coprecipitation reaction. After the obtained liquid was aged for 12 hours, it was centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%).

[0094] Under ice-water bath and stirring conditions, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 3:2), and then 3 mL of pyrrole was added to obtain a solution to be treated;

[0095] 13.69 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0096] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0097] Example 3

[0098] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium chloride and 100 mL of water to obtain a first mixed solution;

[0099] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium chloride and 100 mL of water to obtain a second mixed solution;

[0100] 75 mL of 28% concentrated ammonia water and 100 mL of deionized water were mixed, and the pH value was controlled within the range of 7 to 7.5 using 1 mol / L ammonium chloride solution to obtain a complexing agent solution;

[0101] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min and the complexing agent solution was added dropwise to the first mixed solution at a dropping speed of 1 mL / min. After the addition was completed, the mixture was stirred for 2 hours to perform a coprecipitation reaction. After the obtained liquid was aged for 12 hours, it was centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%).

[0102] Under ice-water bath and stirring conditions, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 3:2), and then 5 mL of pyrrole was added to obtain a solution to be treated;

[0103] 21.3 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0104] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0105] Example 4

[0106] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium chloride and 100 mL of water to obtain a first mixed solution;

[0107] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium chloride and 100 mL of water to obtain a second mixed solution;

[0108] 150 mL of concentrated ammonia water with a mass fraction of 28% and 100 mL of deionized water were mixed, and the pH value was controlled within the range of 7 to 7.5 using an ammonium chloride solution with a concentration of 1 mol / L to obtain a complexing agent solution;

[0109] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min and the complexing agent solution was added dropwise to the first mixed solution at a dropping speed of 1 mL / min. After the addition was completed, the mixture was stirred for 2 hours to perform a coprecipitation reaction. After the obtained liquid was aged for 12 hours, it was centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%).

[0110] Under ice-water bath and stirring conditions, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 3:2), and then 5 mL of pyrrole was added to obtain a solution to be treated;

[0111] 21.3 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0112] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0113] Comparative Example 1

[0114] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium chloride and 100 mL of water to obtain a first mixed solution;

[0115] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium chloride and 100 mL of water to obtain a second mixed solution;

[0116] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min, and the stirring was continued for 2 h after the addition was completed to perform a coprecipitation reaction; the obtained liquid was aged for 12 h, and then centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%);

[0117] Under ice-water bath and stirring conditions, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 3:2), and then 3 mL of pyrrole was added to obtain a solution to be treated;

[0118] 13.69 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0119] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0120] Comparative Example 2

[0121] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium citrate and 100 mL of water to obtain a first mixed solution;

[0122] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium citrate and 100 mL of water to obtain a second mixed solution;

[0123] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min, and the stirring was continued for 2 h after the addition was completed to perform a coprecipitation reaction; the obtained liquid was aged for 12 h, and then centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%);

[0124] Under ice-water bath and stirring conditions, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 3:2), and then 3 mL of pyrrole was added to obtain a solution to be treated;

[0125] 13.69 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0126] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0127] Comparative Example 3

[0128] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium citrate and 100 mL of water to obtain a first mixed solution;

[0129] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium citrate and 100 mL of water to obtain a second mixed solution;

[0130] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min, and the stirring was continued for 2 h after the addition was completed to perform a coprecipitation reaction; the obtained liquid was aged for 12 h, and then centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%);

[0131] Under the condition of ice water bath and stirring, 50 g of iron-based Prussian blue wet material was added into 100 mL of water-alcohol solution (the volume of water and ethanol was 2:3), and then 3 mL of pyrrole was added to obtain the material solution to be treated;

[0132] 13.69 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0133] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0134] Comparative Example 4

[0135] Mix 15.972 g of sodium ferrocyanide, 14.705 g of sodium citrate and 100 mL of water to obtain a first mixed solution;

[0136] Mix 11.12 g of ferrous sulfate, 29.41 g of sodium citrate and 100 mL of water to obtain a second mixed solution;

[0137] At 25° C. and under stirring conditions, the second mixed solution was added dropwise to the first mixed solution at a dropping speed of 2 mL / min, and the stirring was continued for 2 h after the addition was completed to perform a coprecipitation reaction; the obtained liquid was aged for 12 h, and then centrifuged and washed to obtain an iron-based Prussian blue wet material (with a water content of 63%);

[0138] Under the condition of ice water bath and stirring, 50 g of iron-based Prussian blue wet material was added to 100 mL of water-alcohol solution (the volume of water and ethanol was 1:4), and then 3 mL of pyrrole was added to obtain a liquid to be treated;

[0139] 13.69 g of ammonium persulfate was added to 40 mL of deionized water and dissolved, and pre-cooled to obtain an initiator solution at a temperature of 4°C;

[0140] Under stirring conditions, the initiator solution is pumped into the to-be-treated feed solution at a rate of 1 mL / min using a peristaltic pump, and the obtained product is filtered, washed and dried in sequence to obtain the polypyrrole-coated iron-based Prussian blue positive electrode composite material.

[0141] Performance Testing

[0142] Test Example 1

[0143] The polypyrrole-coated iron-based Prussian blue cathode composite material obtained in Example 1 was tested by scanning electron microscopy, and the obtained SEM image is as follows: Figure 1 As shown, from Figure 1 It can be seen that the size of the iron-based Prussian blue coated with polypyrrole has not changed significantly, and it can be seen that there is a uniform polypyrrole coating layer on the surface of the material.

[0144] Test Example 2

[0145] The polypyrrole-coated iron-based Prussian blue cathode composite material obtained in Example 1 was subjected to an X-ray diffraction test, and the obtained XRD pattern was as follows: Figure 2 As shown by Figure 2 It can be seen that the diffraction peak of the polypyrrole-coated iron-based Prussian blue positive electrode composite material obtained in the present invention is sharp and has no impurity phase peak, indicating that the product purity is relatively high.

[0146] Test Example 3

[0147] The polypyrrole-coated iron-based Prussian blue positive electrode composite material obtained in Example 1 was used as a positive electrode material. In a drying room with a dew point below -40°C and a humidity below 10%, the positive electrode material, a binder, and conductive carbon black were mixed in NMP at a mass ratio of 90:5:5, homogenized, and the solid content was controlled to be 45%. The mixture was coated on an aluminum foil current collector, vacuum-baked at 100-110°C for 4-8h, pressed and formed, and then punched to prepare a sodium positive electrode sheet;

[0148] A sodium ion half-cell was assembled with a sodium metal sheet as the negative electrode and 1 mol / L NaPF6 in EC / DMC (Vol 1:1) as the electrolyte; the electrochemical performance of the obtained sodium ion half-cell was tested;

[0149] The first charge and discharge curves obtained at a current density of 0.1C are as follows Figure 3 As shown, from Figure 3 It can be seen that the discharge specific capacity of the material reaches 121.43mAh / g;

[0150] The cycle performance diagram obtained is as follows Figure 4 As shown, from Figure 4 It can be seen that after 60 cycles at a current density of 1C, the capacity retention rate is 94.89%;

[0151] The obtained rate performance diagram is as follows: Figure 5 As shown, from Figure 5 It can be seen that, as a sodium ion battery positive electrode, the polypyrrole-coated iron-based Prussian blue positive electrode composite material obtained in the present invention has very excellent rate performance.

[0152] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a polypyrrole-coated Prussian blue positive electrode composite material, characterized in that: The following steps are involved: mixing sodium ferrocyanide, a first soluble sodium salt and water to obtain a first mixed solution; secondly mixing the soluble divalent transition metal salt, the second soluble sodium salt and water to obtain a second mixed solution; The first mixed solution, the second mixed solution and the third complexing agent are mixed to perform a coprecipitation reaction to obtain a Prussian blue wet material; fourthly mixing the wet Prussian blue material, pyrrole, water and alcohol solvent to obtain a liquid to be treated; fifthly mixing the liquid to be treated and the initiator to obtain the polypyrrole-coated Prussian blue positive electrode composite material; The first soluble sodium salt and the second soluble sodium salt do not include sodium ferrocyanide.

2. The preparation method according to claim 1, characterized in that: The first soluble sodium salt and the second soluble sodium salt independently include one or more of sodium chloride, sodium citrate, sodium alginate, disodium ethylenediaminetetraacetate, sodium oxalate, sodium acetate, sodium gluconate and sodium pyrophosphate.

3. The preparation method according to claim 1, characterized in that: The soluble divalent transition metal salt includes a soluble divalent manganese salt and / or a soluble divalent iron salt.

4. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the sodium ferrocyanide to the first soluble sodium salt is 1:1 to 1.8; The concentration of sodium ferrocyanide in the first mixed solution is 0.16-0.64 mol / L.

5. The preparation method according to claim 1 or 3, characterized in that: The molar ratio of the soluble divalent transition metal salt to the second soluble sodium salt is 1:2-5; The concentration of the soluble divalent transition metal salt in the second mixed solution is 0.32-0.96 mol / L.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The complexing agent includes a nitrogen-containing complexing agent; The molar ratio of sodium ferrocyanide to the complexing agent in the first mixed solution is 0.32:1-2.5; The molar ratio of the sodium ferrocyanide in the first mixed solution to the soluble divalent transition metal salt in the second mixed solution is 0.32:0.4-1.

7. The preparation method according to claim 6, characterized in that: The temperature of the coprecipitation reaction is 0-30°C.

8. The preparation method according to claim 1, characterized in that: The moisture content of the Prussian blue wet material is 60% to 70%; The usage ratio of the Prussian blue wet material to pyrrole is 50g:1-10mL.

9. The preparation method according to claim 8, characterized in that: The alcohol solvent includes one or more of ethanol, methanol and ethylene glycol; The volume ratio of water to alcohol solvent is 1 to 3:1; The concentration of Prussian blue in the liquid to be treated is 0.5-0.7 g / mL.

10. The preparation method according to claim 1 or 8, characterized in that: The initiator includes one or more of ammonium persulfate, hydrogen peroxide, potassium persulfate and sodium persulfate; The mass ratio of the initiator to the Prussian blue wet material is 1-2:10.

Citation Information

Patent Citations

  • Preparation method of nanocarbon coated lithium iron phosphate positive electrode material

    CN106299355A

  • MnO2 / Fe2O3@ amorphous carbon composite material, aptamer sensor and preparation method and application thereof

    CN109813787A